(untitled) (Anclajes, 2022)
This essay analyzes stories published in Los años duros (Jesús Díaz, 1966), Condenados de Condado (Norberto Fuentes, 1968) and Los pasos en la hierba (Eduardo Heras León, 1970) with the goal of characterizing features of the so-called narrative of violence which originated in Cuba in the sixties. Using a critical studies approach, this essay examines this narrative’s distinctiveness in the island’s culture and its connection to intellectual debates at the time of their emergence. It also examines attempts to articulate a distancing from traditional norms of literary potrayal of reality with an original portrayal of the revolution and its combatants. Thus, guidelines adopted by Cuban narrators in their aesthetic practice are defined via their participation in an emancipatory process, yet without forsaking literary autonomy.